Proposed Ownership Structure Design for the Establishment of Waqf Banks in Indonesia - Iwan Agustiawan Fuad; Mohammadtahir Cheumar; Yusuf Haji Othman; Umar Akem (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2025)
Research on waqf banks in Indonesia and other countries shows a significant gap in ownership structure, where previous studies have not provided an applicable ownership design suited for Indonesia's decentralized character. The study is crucial because proper ownership governance can enhance accountability, mitigate conflicts of interest, and improve the economic sustainability of Islamic financial institutions. The research aims to propose an ownership structure of waqf banks in Indonesia. The method employed was qualitative, utilizing a Systematic Literature Review in Evidence-Based Software Engineering. The review covering publications from 2015 – 2024, encompasses 18 articles indexed by Scopus, ERA, WoS, MyCite, Google Scholar, and SINTA, with a process of identification, screening, and thematic analysis. The research findings suggest that establishing a waqf bank in Indonesia necessitates a hybrid ownership structure, backed by clear standard operating procedures, robust regulations, and enhanced community literacy. The implications of this study highlight the need for regulatory revisions and enhanced nāẓir training, while the limitations lie in the lack of empirical validation. Further research is recommended to test the model empirically and analyze the macroeconomic impact of waqf banks on financial inclusion and poverty alleviation.